PEDAGOGICAL COMPETENCE DEVELOPING OF PSYCHOLOGY TEACHER (MASTER’S DEGREE): EXPERIENCE OF UKRAINE - Cherepiekhina , Olha (The Modern Higher Education Review, 2023)
The labour market demands psychologists to be competitive and able to solve professional tasks. In our opinion, competent Psychology teachers should be motivated for professional development in the constantly changing war and post-war times. The article presents the author’s ideas about the development of the pedagogical competence of Psychology teachers (master’s students) in the current conditions of Ukrainian universities, which is the result of a longitudinal scientific and pedagogical study, which began in 2008 on the basis of Ukrainian universities. The changing standards of the teaching profession and the new challenges of the time became the basis for writing this article. The methodology is a literature review which focuses on the analysis of the international experience in training teachers in Psychology. After evaluating international pedagogical and scientific experiences, the author concluded that developing pedagogical competence requires organizing the educational process with a focus on formal, informal, and non-formal methods of obtaining higher education. The text presents a concise overview of the conditions and methods for developing the pedagogical competence of Psychology teachers, including the importance of cultivating reflective abilities as a vital aspect of competence.